Determinants of factors affecting vaccination status of under-five children attending immunoprophylaxis clinic in a tertiary care hospital in central India - Jadhao, Ashok R.; Murari, Hemalatha (International Journal Of Community Medicine And Public Health, 2021)
Background: Immunization is a key to child survival. Immunization is one of the foremost effective and cost-effective ways to protect children’s lives and futures. Despite clear evidence that vaccines save lives and control disease, millions of young children around the world are missing out, putting them and their communities at risk of disease and deadly outbreaks. This is unacceptable in the present era, where affordable, lifesaving vaccines exist. This study aims to study factors influencing timeliness of vaccination and to assess reasons for delay in immunization. Methods: A Cross-sectional study was conducted among mother/caretaker and children (under five years age) attending immunoprophylaxis clinic at a tertiary health care hospital in central India. Total 171 study subjects accompanied by mother/caretaker are included in the study. Analysis was done using SPSS version 20.0. Chi square test and Fischer’s exact test were used to find the association between characteristics of study subjects and obstetric variables with delayed vaccination. Results: Delayed Vaccination is present in 119 (69.6%) of study subjects. Among the reasons for delayed vaccination, majority were parent related reasons which was present among 84 (70.6%) of study subjects. The association of higher birth order with delayed vaccination was found to be statistically significant. Conclusions: The overall delayed vaccination was present in 69.6% of children and high birth order (3 or more) has a significant association with delayed immunization.